Design And Implementation of LAN Commander Applicable For Efficient Network Administration Solution Using JAVA Programming - Parthasarathy, Rajamohan; Rajamanickam, Leelavathy; Loong, Seow Soon; Ayyappan, Preethy; Saidawi, Hazim Al (International Journal of Psychosocial Rehabilitation, 2020)
The defining factor of our today world is communication technology and particularly, the Internet; that vast multitude of computer networks that came together to become a meaningful whole. Our world of now relies upon those networks, and the expansion and scaling of those networks is always underway, trying to keep ahead of the ever-growing needs of large companies and organizations. As these networks grow, the number of technical challenges that maintaining them grows as well. Depending on the size, a single company may house dozens or hundreds or even more subnets, and all must be kept in check, to make sure that the organization’s work goes ahead unhindered. The latter lines basically describe how the job of “Network Administrator” came to be overcome. They are the first and perhaps only line of defense against unforeseen circumstances that may hinder the operations of an organization and although it seems straightforward on paper, the sheer amount of network end devices makes their task seem impossible at a glance. This paper aims to facilitate the operation of Computer Networks, by allowing Network Administrators to remotely manage endpoints through means of a Java Software called “LAN Commander”. This function will allow for various features, such as Remote Desktop control and Network Monitoring.